2013
DOI: 10.1002/mats.201300118
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution in Linear Low Density Polyethylene During Peroxide Modification: A Monte Carlo Simulation Study

Abstract: A Monte Carlo (MC) simulation is performed on peroxide induced branching reactions in a linear low density polyethylene (LLDPE) melt processed with different dicumyl peroxide (DCP) concentrations at various processing times and temperatures. The MC simulation can successfully monitor the microstructural changes due to the induced long chain branching (LCB), decreased terminal double bonds, and increased trans vinyl bonds in LLDPE during peroxide modification. The induced structural changes are in good agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
(190 reference statements)
0
6
0
Order By: Relevance
“…It is to be noted that the unusual upturn may also be due to formation of radicals and reactions between the two polyolefins however, our recent investigations on melt mixing of polyethylenes (PEs) with peroxides in order to produce branched and crosslinked PEs, showed that the measured gel contents were very negligible even in presence of peroxides at low contents and no degradation occurred up to 300 °C. Based on these results, we can conclude that under the processing conditions used for the current work, i.e., 250 °C the formation of radicals and reactions between the HDPE and PP is not likely to happen.…”
Section: Resultsmentioning
confidence: 99%
“…It is to be noted that the unusual upturn may also be due to formation of radicals and reactions between the two polyolefins however, our recent investigations on melt mixing of polyethylenes (PEs) with peroxides in order to produce branched and crosslinked PEs, showed that the measured gel contents were very negligible even in presence of peroxides at low contents and no degradation occurred up to 300 °C. Based on these results, we can conclude that under the processing conditions used for the current work, i.e., 250 °C the formation of radicals and reactions between the HDPE and PP is not likely to happen.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, by using the MC simulation, the variations of pendent, terminal, and trans vinyl groups during peroxide modification were reported. It was reported that the concentration of terminal double bonds decreased in the course of modification whereas that of trans double bonds increased.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation, Monte Carlo (MC) simulation were performed on peroxide‐induced branching reactions in an LLDPE melt processed with different dicumyl peroxide (DCP) concentrations at various processing times and temperatures. The MC simulation could successfully monitor the microstructural changes due to the induced LCB, decreased terminal double bonds, and increased trans vinyl bonds in LLDPE during peroxide modification.…”
Section: Introductionmentioning
confidence: 99%
“…Golriz et al used a MC model to study how dicumyl peroxide (DCP) changed the microstructure of linear low‐density polyethylene (LLDPE) using different DCP concentrations, processing times, and temperatures. In their proposed mechanism, the dominant steps were DCP decomposition, hydrogen abstraction, and chain termination by combination.…”
Section: Stochastic Simulation Algorithms (Ssa)mentioning
confidence: 99%